Penyelesaian Sengketa dalam Pengadaan Tanah Bagi Pembangunan Jalan untuk Kepentingan Umum - Fengky Kotalewala; Adonia Ivone Laturette; Novyta Uktolseja (SASI, 2020)
Land acquisition for the construction of roads in the public interest is a classic problem that always creates turmoil in the community. This study aims to analyze land acquisition followed by land acquisition belonging to the people, always causing disputes that sometimes lead to violence or at least lead to court. The research method used normative research with a statute approach and a conceptual approach and analyzed descriptive qualitative. Based on the Research Results, it is indicated that Settlement of disputes in Land Procurement for Road Development in the public interest should be carried out to the maximum extent possible through consultation and / or through non-litigation or settlement outside the Court. Land Procurement for Development for public purposes, give Honor to holders Land Rights by providing legal protection and by providing fair and appropriate compensation to the rightful parties, but in reality often the holders of the rights granted experience a decline in quality compared to the original situation before the release of land rights.